Overview of Traffic Police Knowledge About Basic Life Support (BLS) at Ciamis Police Station - Dadi Hamdani; Rudi Kurniawan; Faisal Reza Muhammad; Sandriani (Jurnal Vocational Nursing Sciences (VNUS), 2020)
Objective: The number of deaths from traffic accidents over the years ever-increasing. According to the Global Status Report on Road Safety, more than 1.2 million people die annually due to traffic accidents, with millions more getting a serious injuries. The number of victims resulting from transportation accidents (traffic) that give rise to emergency conditions, need help quickly on the scene to prevent the morbidity and mortality of the victim. The traffic police is an apparatus that served to safeguard the safety of road users and minimize traffic accident victims. Method: This research aims to know the description of knowledge of traffic police about the assistance of Basic Life Support way of breath in Police Resort Ciamis. The research method used i.e. descriptive. The population in this study are all the police officers in the traffic Office Police Resort Ciamis as many as 120 people. Samples were taken using the technique of proportional random sampling. Result: The research results showed that the knowledge of respondents about the sense of the highest frequency of knowledge category Basic Life Support enough i.e. as many as 36 people (66.7%). The knowledge of respondents about the purpose and the initial steps of the highest frequency of good category Basic Life Support. that is as many as 37 people (68.5%). The knowledge of respondents about the stages of Basic Life Support way breath (airway) frequency-the highest category of good that is as many as 27 people (50.0%). Conclusion: The conclusions of the research on knowledge description of traffic police of traffic police  about the assistance of Basic Life Support in Police Resort Cimias the highest frequency of good category i.e. as many as 28 people (51.8%).